Social Structure, Power, and Justice: An Analysis of Structural Inequality - Judijanto, Loso; Fadhilah, Nurul (PT. Anagata Sembagi Education, 2026)
This study examines the relationship between social structure, power distribution, and justice in the context of structural inequality in Indonesia. Structural inequality persists across various sectors, including natural resource governance, law enforcement, and access to education, indicating that injustice is embedded within institutional arrangements rather than arising solely from individual factors. This research aims to critically analyze how social structures distribute power and reproduce inequality, and to assess their implications for substantive social justice. The study employs a qualitative design using a critical socio-legal and political economy approach. Data were collected through document analysis, in-depth interviews, and cross-case comparison across selected contexts, including mining governance, environmental enforcement, and education access. The data were analyzed using thematic coding and interpretative analysis to identify recurring structural patterns of inequality. The findings reveal that centralized authority, capital dominance, and unequal institutional access systematically marginalize vulnerable groups. Inequality manifests in asymmetrical law enforcement, exclusion from decision-making processes, and uneven resource distribution. The discussion highlights that justice cannot be understood merely in procedural terms but must address substantive redistribution and structural reform. In conclusion, structural inequality is sustained by entrenched power configurations, and achieving social justice requires institutional transformation and equitable redistribution of power and resources.